2019
DOI: 10.3390/su11205736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Network Embeddedness and Network Diversity on Green Innovation: The Mediation Effect of Green Social Capital

Abstract: Due to the current rise in concern about the challenge of global warming, stakeholders are now more conscious than in the past regarding environmental concerns. Stakeholders are more likely than ever before to support companies that are environmentally friendly. Simultaneously, companies seek to develop their social networks in such a way as to enhance their green innovation. This study investigates the influences of network embeddedness and network diversity on green innovation. In addition, this research dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 80 publications
4
22
0
Order By: Relevance
“…In addition to innovative products, GRC mediated the relationship between network embeddedness and green innovation performance (meant as the performance reached through the organization's green innovation) [47]. This means that network embeddedness can affect green innovation performance both directly and through green social capital [62]. The association between GRR and environmental performance was confirmed by two recent studies, that reported a direct link between the two [65], as well as a mediated link by means of GHRM practices [83].…”
Section: Outcomes Of Single Dimensions Of Gicsupporting
confidence: 52%
See 3 more Smart Citations
“…In addition to innovative products, GRC mediated the relationship between network embeddedness and green innovation performance (meant as the performance reached through the organization's green innovation) [47]. This means that network embeddedness can affect green innovation performance both directly and through green social capital [62]. The association between GRR and environmental performance was confirmed by two recent studies, that reported a direct link between the two [65], as well as a mediated link by means of GHRM practices [83].…”
Section: Outcomes Of Single Dimensions Of Gicsupporting
confidence: 52%
“…The remaining six studies either addressed GIC as a general construct (N = 2), thus calculating a general "green intellectual capital" score [57,58], or focused on specific GIC dimensions of the tripartite model of IC (N = 8), thus focusing on human [47,[59][60][61], on social capital [62], on structural capital [63], on organizational and social capital [64], or on human and relational capital [65].…”
Section: Gic Constructmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, cooperation with suppliers and universities is significantly associated with the probability of environmental innovation, while cooperation with customers does not lead to any important difference. More recently, Chen et al (2019) examined the effects of networks on green innovation. Their study illustrates that network embeddedness and network diversity are positively associated with green innovation performance.…”
Section: Networkmentioning
confidence: 99%